2016
DOI: 10.1021/acs.est.5b04110
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bioavailability, Bioaccessibility, and Dermal Absorption of PAHs from Soil—State of the Science

Abstract: This article reviews the state of the science regarding oral bioavailability, bioaccessibility, and dermal absorption of carcinogenic polycyclic aromatic hydrocarbons (cPAHs) in soil by humans, and discusses how chemical interactions may control the extent of absorption. Derived from natural and anthropomorphic origins, PAHs occur in a limited number of solid and fluid matrices (i.e., PAH sources) with defined physical characteristics and PAH compositions. Existing studies provide a strong basis for establishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 105 publications
1
54
0
Order By: Relevance
“…The relative oral bioavailability (bio accessibility) of each metal in dust particles was determined using the In vitro method as described by Ruby et al [16] and Oomen et al [23]. The method is a two-step physiological based extraction test that investigates the solubility of metals in laboratory test.…”
Section: Bio Accessibility (Oral Bioavailability) Testmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative oral bioavailability (bio accessibility) of each metal in dust particles was determined using the In vitro method as described by Ruby et al [16] and Oomen et al [23]. The method is a two-step physiological based extraction test that investigates the solubility of metals in laboratory test.…”
Section: Bio Accessibility (Oral Bioavailability) Testmentioning
confidence: 99%
“…According to Ruby et al [15], some metals and their compounds are not readily soluble; therefore toxicity tests based on their solubility may overestimate the health risk associated with them. Bioaccessibility is a closely related term which refers to the fraction of contaminant that is dissolved in the digestive fluids and assumed to be available for absorption and bioavailable [16]. Similarly, it has also been reported that total concentration of metals can reflect the pollution level of dust, but cannot predict its bioavailability [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these screening levels are exceeded, multiple research studies suggest that PAHs in soil have soil ingestion bioaccessibility <50%, and this finding indicates that bioaccessibility assessment may be included in site‐specific risk assessments rather than relying on total contamination concentration only (Ruby et al, 2016). Bioaccessibility refers to the amount of contaminant extracted in a laboratory test (in vitro) that can be used to estimate the contaminant uptake that would occur in an animal study (Ruby et al, 2016). Bioavailability refers to the amount of contaminant measured in an animal uptake study (in vivo), and this contaminant amount can be described in absolute concentration or a concentration relative to a standard contaminant material (Ruby et al, 2016).…”
mentioning
confidence: 99%
“…Bioaccessibility refers to the amount of contaminant extracted in a laboratory test (in vitro) that can be used to estimate the contaminant uptake that would occur in an animal study (Ruby et al, 2016). Bioavailability refers to the amount of contaminant measured in an animal uptake study (in vivo), and this contaminant amount can be described in absolute concentration or a concentration relative to a standard contaminant material (Ruby et al, 2016). With well‐established regression equations between bioaccessibility and bioavailability data, bioaccessible tests can be used to help predict contaminant uptake in a variety of new soils without conducting in vivo studies for each new soil.…”
mentioning
confidence: 99%